Managing personal and professional roles: comparative study on professional mobility of women teachers in india and sri lanka - Kugamoorthy, S. (University of Jaffna, 2012)
With an increased participation in higher education, women are entering the work force in all sectors in larger numbers. Therefore, the status of women has improved to some extent. But in the family/society the most commonly held stereotyped view of women is that they should limit their activities to the role of a home-maker, wife and mother. Currently, there are many factors which remain as obstacles in the women teacher’s upward mobility in an institution. This study attempts to find out the factors influencing women teachers to manage their personal and professional roles for their professional mobility. Quantitative research approach was used in this study within a framework of a survey research design. This study was conducted on women teachers, at primary, secondary and tertiary levels of education in two different socio-cultural contexts i.e. India and Sri Lanka. This study was undertaken in the Sivagangai District of Tamil Nadu, India and Colombo District, Sri Lanka. Among the total sample of 600 women teachers, 494 women teachers responded to this study. The sample included 240 women teachers from Sivagangai District, Tamil Nadu, India and 254 women teachers from Colombo District, Sri Lanka. Two types of instruments were used for data collection namely (a) Professional Mobility Aspiration Scale (PMAS) and (b) Professional Mobility Determinants Inventory (PMDI). The dependent variable of the study is professional mobility aspiration, and independent variables are personal factors and institutional factors. The data obtained were tabulated and analyzed applying statistical techniques such as percentage and chi-square. The study revealed that among the personal factors, role conflict as a working woman, a wife and a mother, child care, child education, care of family and family- work conflict emerge while among the institutional factors work load, limited promotional opportunities, official bottlenecks, work-family conflict and lack of work recognition are major barriers for their aspiration for promotions are noted. In both the countries both personal factors and institutional factors are significantly associated with professional mobility of women teachers at 0.01 level. It is understood that due to various personal and professional reasons women teachers need to manage their family-work conflict and work-family conflict for their professional mobility. Overall, the analysis appears to suggest that women teachers should develop appropriate time management behavior to balance their multiple roles performed in their family life and professional life.
Keywords: Women teachers; Professional mobility; Personal roles; Professional roles